URGENSI REFORMASI PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA NARKOTIKA: ANTARA REHABILITASI DAN PENJARA - Anastasia Sarjono (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
This study aims to analyze the urgency of criminal reform against perpetrators of narcotics crimes, especially users, with a focus on the Gorontalo Province area. In practice, the criminal justice system in this area still tends to impose prison sentences on narcotics users, although Law Number 35 of 2009 on Narcotics opens up space for a rehabilitation approach. This study uses an empirical juridical method with a qualitative approach, involving interviews with law enforcement officials, rehabilitation officers, and observations at correctional institutions and BNNP Gorontalo. The results of the study show that the implementation of rehabilitation is still limited due to weak coordination between agencies, limited resources, and the non-optimal implementation of integrated assessments. As a result, many users are overcriminalized and lose the opportunity to recover socially and medically. This study emphasizes the need for criminal policy reform through a more humanistic, public health-based, and rehabilitative-oriented approach, not just punishment